1996
DOI: 10.1074/jbc.271.12.6889
|View full text |Cite
|
Sign up to set email alerts
|

Unequivocal Identification of Asp-214 as the Catalytic Nucleophile of Saccharomyces cerevisiae α-Glucosidase Using 5-Fluoro Glycosyl Fluorides

Abstract: Yeast ␣-glucosidase is a member of a sequence-related family of ␣-glycosidases (Family 13) that includes important digestive ␣-amylases and ␣-glucosidases. These enzymes catalyze the hydrolysis of ␣-linked oligosaccharides by a two-step mechanism involving a glycosylenzyme intermediate. This Glycosyl hydrolases of Family 13 (the ␣-amylase family (1, 2)), which include ␣-amylases and some ␣-glucosidases and oligo-1,6-glucosidases, are important enzymes involved in the digestion of starch and other ␣-linked olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 17 publications
9
90
0
1
Order By: Relevance
“…Replacement of these residues with other amino acids affected the function of WecA, as demonstrated by the lack of in vitro enzymatic activity or reduced in vitro enzymatic activity of the mutated proteins, which could not mediate O-antigen LPS production in vivo (4). Aspartic acids have nucleophilic side chains, which may be involved in binding divalent metal ions (most commonly Mn 2ϩ or Mg 2ϩ ) or in catalysis (23,47,59), as shown previously for other glycosyl and prenyl transferases (10,33,34,50). We hypothesized that Asp90, Asp91, Asp156, and Asp159 are important for the catalytic activity of WecA (4).…”
mentioning
confidence: 79%
“…Replacement of these residues with other amino acids affected the function of WecA, as demonstrated by the lack of in vitro enzymatic activity or reduced in vitro enzymatic activity of the mutated proteins, which could not mediate O-antigen LPS production in vivo (4). Aspartic acids have nucleophilic side chains, which may be involved in binding divalent metal ions (most commonly Mn 2ϩ or Mg 2ϩ ) or in catalysis (23,47,59), as shown previously for other glycosyl and prenyl transferases (10,33,34,50). We hypothesized that Asp90, Asp91, Asp156, and Asp159 are important for the catalytic activity of WecA (4).…”
mentioning
confidence: 79%
“…It has been suggested that the aspartic acid residues identified in sucrase-isomaltase and lysosomal ␣-glucosidase constitute the catalytic nucleophile in this family. However, as already noticed, the assignment of the role played in catalysis by these residues remains equivocal (40). In fact, conduritol epoxide derivatives occasionally have labeled active site residues different from the nucleophile, and the levels of residual enzymatic activity of the human lysosomal ␣-glucosidase mutant Asp-518 3 Asn was incompatible with the essential function proposed (39).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Ima1p and Ima2p exhibit the same GEMQH consensus, whereas the Ima3p and Ima4p consensus is GEMRH, and the Ima5p consensus diverges from the others with the GEVGI sequence. The Asp residue in region II has been described as the catalytic nucleophile of ␣-glucosidases, whereas Glu (region III) and Asp (region IV) are likely involved in acid/base catalysis (31). The only pertinent difference between the five putative ␣-glucosidases encoded by YGR287c, YIL172c (id.…”
Section: Identification Of Five Genes Encoding Putative ␣-16-mentioning
confidence: 99%